Isolated spinal accessory neuropathy and intracisternal schwannomas of the spinal accessory nerve - Abdullah M. Al-Ajmi; Rossen T. Rousseff; Todor Shamov; Mohammad J. Ismail; Faisal T. Sayer (Interdisciplinary Neurosurgery, 2015)
We report a 40-year-old female patient presenting with isolated left spinal accessory neuropathy that developed insidiously over 6 years. She complained of ill-defined deep neck and shoulder pain. On examination, prominent sternocleidomastoid and trapezoid muscle weakness and atrophy, shoulder instability, and lateral scapular winging were observed. MRI identified a small mass of the cisternal portion of the spinal accessory nerve. Its appearance was typical of schwannoma. Surgical treatment was not offered because of the small tumor size, lack of mass effect and the questionable functional recovery in the presence of muscular atrophy.